Residência pedagógica: interação escola e universidade para o ensino de ciências e matemática - Oliveira, Marcelo Parreira de (2024)
Teacher training and the implementation of effective public policies are essential to improve the quality of Basic Education. The general objective of this research was to analyze the training actions carried out with the immersion of residents who participated in the Pedagogical Residency Program (PRP) of the Federal University of Uberlândia (UFU), from 2020 to 2022, according to Notice No. 01/2020, of the Coordination for the Improvement of Higher Education Personnel (CAPES), in the Interdisciplinary Subproject of the Physics, Mathematics and Chemistry center, on the Ituiutaba campus. The research had a qualitative approach, using documentary analysis of the reports of the residents as the main methodological procedure. In order to analyze this research, we set up three guiding lines, being them: (1) strengthening teacher training; (2) design and pedagogical practices of the Pedagogical Residency Program for teacher training; and (3) interaction to promote teacher training. As part of the process, an educational product was developed: a quiz for teaching Science and Mathematics, developed together with a resident of the proposed notice issued, with the intention of enhancing teacher training. Through the analyses conducted, it can be inferred that the PRP, by promoting interaction between school and university, focusing on the articulation between theory and practice, contributed to the qualification of future teachers, allowing them to experience different pedagogical practices in the context of basic education, strengthening teacher training.